A real-time immuno-PCR assay for the detection of tetrabromobisphenol A. Issue 1 (30th October 2014) - Bu, Dan; Zhuang, Huisheng; Yang, Guangxin; Ping, Xianyin
Abstract : In this study, a reliable and ultra-sensitive indirect competitive real-time immuno-PCR (rt-iPCR) was established for the determination of tetrabromobisphenol A (TBBPA). Abstract : In this study, a reliable and ultra-sensitive indirect competitive real-time immuno-PCR (rt-iPCR) was established for the determination of tetrabromobisphenol A (TBBPA). The optimal hapten, artificial immunogen, coating antigen, and polyclonal anti-TBBPA antibodies were successfully prepared. For optimizing rt-iPCR, several physiochemical factors, such as optimal coupling concentration of immunogen and antibody, and the amounts of streptavidin and biotinylated DNA, are discussed. Using this proposed rt-iPCR assay, TBBPA could be determined in the range from 10 pg L −1 to 10 ng L −1, with a detection limit of 2 pg L −1 . This rt-iPCR was selective, with low cross-reactivity with TBBPA analogs. Finally, seabed sediment samples were analyzed by rt-iPCR and liquid chromatography. The tested results were demonstrated to be receivable and accurate. The average recovery was between 89.8% and 113.6%. We think this developed rt-iPCR will be very useful in the field of environmental science.